Geochemical characterization of Lokoja-Basange Sandstone at Imiegba and Okpekpe areas, Benin flank of Anambra basin, Nigeria: implications for provenance, tectonic setting and source-rock weathering - Omale Obaje , Solomon; Adekunle Adefemisoye , Alex (International Journal of Advanced Geosciences, 2024)
This study investigates the geochemical attributes of the Lokoja-Basange Sandstone situated in Okpekpe and Imiegba areas of the Benin Flank of Anambra Basin, Nigeria. The aim of this study is to unveil its provenance, tectonic setting, and source rock weathering extent. Using energy dispersive x-ray fluorescence (EDXRF) "Minipal 4" spectrometer analysis, nine outcrop samples were examined for major oxide concentrations. The results show significant average SiO2 (77.09 wt. %), Al2O3 (12.10 wt. %), Fe2O3 (2.72 wt. %), Na2O (1.64 wt. %), K2O (2.41 wt. %), while TiO2, MnO, MgO, CaO, P2O5, LOI had average concentrations of less than 1.00 wt. %. Bivariate plots of log [Fe2O3/K2O] versus log [SiO2/Al2O3] indicate 77.80% litharenites and 22.20% arkose sediments. The [Al2O3]-[CaO+Na2O]-[K2O] ternary plot, the tectonic discriminant diagrams of [SiO2/20]-[K2O+Na2O]-[TiO2+Fe2O3+MgO], log [K2O/Na2O] versus SiO2, [SiO2/Al2O3] versus log [K2O/Na2O] and bivariate discriminant functions plot indicate that the sediments have felsic igneous provenance and quartzose sedimentary origin, within a passive margin tectonic setting and the source-area underwent moderate to near complete chemical weathering in semi-arid to humid climatic conditions with increasing chemical maturity. Conclusively, the chemical alteration index (CIA) ranges from 65.4% to 74.2%, averaging 70.70%; the chemical index of weathering (CIW) averages 82.37%; the plagioclase index of alteration (PIA) averages 78.88%; and the mineralogical index of alteration (MIA) averages 41.43%. These data signify extensive weathering of felsic igneous source rocks, highlighting mineralogical maturity of Lokoja-Basange Sandstone. In essence, this study enriches insights into the sandstone's origins, sedimentary context, and weathering history.